2014
DOI: 10.1186/1471-2407-14-487
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the epithelial-mesenchymal transition by SHARP1 is linked to the NOTCH1 signaling pathway in metastasis of endometrial cancer

Abstract: BackgroundMechanisms governing the metastasis of endometrial cancer (EC) are poorly defined. Recent data support a role for Enhancer-of-split and hairy-related protein 1 (SHARP1), a basic helix-loop-helix transcription repressor, in regulating invasiveness and angiogenesis of several human cancers. However, the role of SHARP1 in metastasis of EC remains unclear.MethodsHuman EC cell lines (Ishikawa and HEC-1B) were used. SHARP1 was upregulated by lentivirus transduction, while intracellular domain of NOTCH1 (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Pertinently, SHARP1 was found to play a critical role in malignant progression and acquisition of metastatic phenotypes in EC. A positive correlation was detected between SHARP1 and E-cadherin levels and negative correlation between SHARP1 and levels of JAG1, SNAIL, and vimentin (Liao et al 2014b). While a few investigators have reported downregulated expression of Notch signaling molecules (Jonusiene et al 2013, Sasnauskiene et al 2014, others found a significantly higher expression of Notch related molecules in EC as compared to normal endometrium (Mitsuhashi et al 2012).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 89%
“…Pertinently, SHARP1 was found to play a critical role in malignant progression and acquisition of metastatic phenotypes in EC. A positive correlation was detected between SHARP1 and E-cadherin levels and negative correlation between SHARP1 and levels of JAG1, SNAIL, and vimentin (Liao et al 2014b). While a few investigators have reported downregulated expression of Notch signaling molecules (Jonusiene et al 2013, Sasnauskiene et al 2014, others found a significantly higher expression of Notch related molecules in EC as compared to normal endometrium (Mitsuhashi et al 2012).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 89%
“…[26][27][28] After validation by RT-qPCR of miRNA selected from the previous step, we found that miR-34b-5p, miR-34c-5p, miR-34c-3p, miR-375, and miR-184 emerged as being particularly relevant to determine positive or negative LN metastatic status in women with grade 1-2 early-stage EC. Furthermore, miR34b-5p, miR-34c-5p, miR-34c-3p, and miR-184 dominated the first principal component of the principal component analysis.…”
Section: Discussionmentioning
confidence: 99%
“…SK‐N‐SH and QDDQ‐NM cells were seeded in a 24‐well plate at a density of 1 × 10 4 cells/well in 500 ÎŒL complete culture solution. When cell confluence reached 60–80%, the cells were transducted according to the lentivirus transduction manual; the purpose of the transduction was to upregulate the Beclin 1 and TRP14 genes and to establish Beclin 1 high and TRP14 high tumor cells, as previously described . The empty vector LacZ was used as a control construct.…”
Section: Methodsmentioning
confidence: 99%
“…When cell confluence reached 60-80%, the cells were transducted according to the lentivirus transduction manual; the purpose of the transduction was to upregulate the Beclin 1 and TRP14 genes and to establish Beclin 1 high and TRP14 high tumor cells, as previously described. (33) The empty vector LacZ was used as a control construct. Beclin 1 high and TRP14 high NB cells were treated with 10 nM PTX and 0.25 lmol/L SAHA.…”
Section: Methodsmentioning
confidence: 99%